The impact of access to sanitary toilets on rural adult residents' health: Evidence from the China family panel survey - Baoqi Chen; Fulei Jin; Yaxin Zhu (Frontiers Media S.A., 2022)
Toilet sanitation is related to public health and environmental protection. In the context of the toilet revolution in rural China, an ordered probit regression analysis was conducted to evaluate the impact of access to sanitary toilets on rural residents' health. Using data from the China Family Panel Study (CFPS) in 2014, we found that access to sanitary toilets in rural households significantly improved residents' health, and this finding remained robust across a series of checks. Meanwhile, results of the mechanism analysis showed that preventing feces from contaminating water sources was an important mechanism behind the positive effects of sanitary toilet use on health. We also found that the impact of access to sanitary toilets was more pronounced among female, middle-aged, and low-income people. Toilet revolution plays an important role in ensuring residents' health and protecting water sources, thereby underscoring the need for governments in developing countries to invest in sanitary toilets. In addition, the existing policies and sanitation programs in China need to be improved to promote public health.